Venture capital and the changing world of entrepreneurship - Butler, John E., 1946-; Lockett, Andy; Ucbasaran, Deniz (Research in entrepreneurship and management., 2006)
It was not that long ago that it might have been possible to cover the topic of venture capital in one paper. Now, it is not possible to provide comprehensive coverage in even one book. The industry has flourished, as variations of he initial venture capital funds have been developed and now operates in most developing and developed economies. This is clearly reflected in this volume, which has a strong focus on Europe and Asia. Each of the papers is a stand alone effort. However, a full reading of the volume provides a panoramic picture of the global extent of venture capital, some of its challenges, and the likely direction of future efforts. Venture capital and the venture capitalist have been shown to have a positive impact on performance in many cases. This is clearly the reason why some many emerging economies want to increase the level of venture capital investment in their country.